Establishing Cultural Fronts in East and West Germany. (June 2016) - Brockmann, Stephen
Abstract : This paper examines the development of German postwar culture in the eastern and western zones as a function of the felt need to use culture in the denazification of Germany. The Kulturbund (Cultural Federation for the Democratic Renewal of Germany), founded by the exile writer Johannes R. Becher in 1945, was the primary institutional expression of this concern, which was widespread among the four occupying powers and German anti-Nazis. At the same time, however, there was a strong feeling in the postwar period that traditional German culture itself needed to be called into question and transformed because of its previous failure to prevent the triumph of Nazism. The paper explores the initial antifascist consensus, characterized by broad cooperation among the occupying powers and relative cultural conservatism, and the way that this consensus began to break down in 1947 under the pressures of the emerging Cold War. This breakdown led to increasing emphasis, after 1947, on the need to transform culture itself, and to growing criticism of traditional cultural conservatism. This emphasis was particularly strong in the western parts of Germany and differentiated the west from the east. It received institutional expression in the creation of the Congress for Cultural Freedom in 1950.